2014
DOI: 10.14356/kona.2014015
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Fabrication of Complex Shaped Metal Oxide Nano-Microstructures and Their Interconnected Networks for Multifunctional Applications

Abstract: Metal oxide nano-microstructures are applied in photocatalytic surfaces, sensors or biomedical engineering, proving the versatile utilization of nanotechnology. However, more complex or interconnected nano-microstructures are still seldomly met in practical applications, although they are of higher interest, due to enhanced structural, electronic and piezoelectric properties, as well as several complex biomedical effects, like antiviral characteristics. Here we attempt to present an overview of the novel, faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(60 citation statements)
references
References 70 publications
(126 reference statements)
0
60
0
Order By: Relevance
“…Not only perovskite glass ceramics can play important role in energy storage application but few metal oxide based ceramics are also useful. Mishra et al [20,21] have reported the ZnO based ceramics and which contains nano particles.…”
mentioning
confidence: 99%
“…Not only perovskite glass ceramics can play important role in energy storage application but few metal oxide based ceramics are also useful. Mishra et al [20,21] have reported the ZnO based ceramics and which contains nano particles.…”
mentioning
confidence: 99%
“…This indicates that zinc acetate dehydrate is hydrolyzed to Zn(OH) 2 in 2-methoxyethanol solvent. The reactions involved at this stage can be described as two reversible hydrolysis reactions (1) and (2). Second, stabilizer MEA was then added to the complex solution and stirred at 60…”
Section: Mechanism For the Reactions Involved In The Sol Solution Prementioning
confidence: 99%
“…In recent years, study on the ZnO is increasingly attractive because ZnO has a direct wide-band gap of 3.37 eV and a large exciton binding energy of approximately 60 meV [1,2]. Owning to its excellent physical properties, ZnO has been a promising material in piezoelectric and optoelectronic fields [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thorough reviews on the flame spray pyrolysis (FSP) techniques for producing nanopowder have been made previously (Pratsinis, 1998;Mädler, 2004;Teoh et al, 2010). The FSP method generates well-defined nanoparticulate material which can be collected as a powder from the exhaust aerosol of the flame (Stepuk et al, 2013;Park and Park, 2015) or sprayed on a surface (Mishra et al, 2014). Apart from nanopowder production, recently the FSP and related techniques have also been used fairly efficiently in various types of coating applications (Mädler et al, 2006a;Tricoli et al, 2008;Pimenoff et al, 2009).…”
Section: Introductionmentioning
confidence: 99%